2017
DOI: 10.1016/j.seizure.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes about epilepsy: A survey of high school students in Germany

Abstract: To improve knowledge and attitudes and reduce misconceptions further education seems necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 21 publications
1
12
1
Order By: Relevance
“…Between 2005 and 2013, the percentage of people who said they would be nervous around people with epilepsy increased [6]. In a German survey of more than 1000 students aged approximately 14 years, one-fifth of the participants reported that they would not want to go on a romantic date with a person with epilepsy [12]. Parents of children with epilepsy and developmental disorders reported discrimination against their children [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2005 and 2013, the percentage of people who said they would be nervous around people with epilepsy increased [6]. In a German survey of more than 1000 students aged approximately 14 years, one-fifth of the participants reported that they would not want to go on a romantic date with a person with epilepsy [12]. Parents of children with epilepsy and developmental disorders reported discrimination against their children [21].…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier survey, a quarter of pediatric epilepsy patients reported that they thought they were generally worse off than healthy children [18]. A number of healthy adolescents still have reservations about, for example, being in a romantic relationship with a person with epilepsy [12]. Such reservations could prompt pediatric epilepsy patients to conceal their condition, but having to conceal something as important as a chronic condition can put enormous stress on patients.…”
Section: Introductionmentioning
confidence: 99%
“… 5 6 A range of incorrect and even harmful practices to regulate seizure are frequently embraced; for instance, keeping iron rod in the hand, rubbing irritants to eyes, holding the patient in fire, burns, and ingestion of cow urine. 7 8 9 It is imperative to educate about management of this chronic disease to the caregivers and patients with epilepsy to improve self-care. 10 11 12 …”
Section: Introductionmentioning
confidence: 99%
“…As a number of children with epilepsy already feel worse off than healthy children (Pauschek et al, 2016), adverse drug events, such as challenging behaviour, can increase the difficulties associated with social integration. In a German study, 3% of high school students even stated that they would not want to be friends with Physicians' experiences of epilepsy a person suffering from epilepsy (Jansen et al, 2017). In older age, adverse drug events, such as dizziness, unsteady gait, and falls, might become more relevant, as the prevalence of falls increases with age (Peeters et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the extent of knowledge and experiences regarding these issues. These have focussed on teachers (Dumeier et al, 2015;2017a;2017b), parents (Lewis et al, 2010;Bertsche et al, 2013;Spindler et al, 2017), patients (Lewis et al, 2010;Bertsche et al, 2013;Spindler et al, 2017), patients (Lewis et al, 2010;Pauschek et al, 2016;Kadel et al, 2018), or the public (Fong and Hung, 2002;Kartal and Akyıldız, 2016;Jansen et al, 2017). A recent study investigated the educational needs of physicians working in paediatric epileptology with emphasis on neurologists and neuropaediatricians (Murray et al, 2018).…”
mentioning
confidence: 99%